Employment-Related Factors of Forensic Psychiatric Outpatients with Psychotic Disorders - Takeda K (Dove Medical Press, 2019)
Koji Takeda,1,2 Norio Sugawara,3 Yuji Yamada,1 Takako Nagata,1 Hiroko Kashiwagi,1 Toshiaki Kono,4 Naotsugu Hirabayashi,1 Takayuki Okada2 1Department of Psychiatry, National Center of Neurology and Psychiatry Hospital, Kodaira, Tokyo 187-8551, Japan; 2Section of Psychiatry and Behavioral Sciences, Graduate School of Medical and Dental Sciences, Tokyo Medical and Dental University, Tokyo 113-8510, Japan; 3Department of Psychiatry, Dokkyo Medical University School of Medicine, Tochigi 321-0843, Japan; 4Department of Community Mental Health and Law, National Institute of Mental Health, National Center of Neurology and Psychiatry, Kodaira, Tokyo 187-8553, JapanCorrespondence: Koji TakedaDepartment of Psychiatry, National Center of Neurology and Psychiatry Hospital, 4-1-1 Ogawa-Higashi, Kodaira, Tokyo 187-8551, JapanTel +81 42 341 2711Fax +81 42 344 6745Email ideakojijan@ncnp.go.jpPurpose: Employment is important for forensic psychiatric patients with psychotic disorders, in terms of reduction in symptoms, improving the quality of life, and preventing re-offenses. However, few detailed studies on employment status in such patients exist. We aimed to determine the employment rate among forensic psychiatric outpatients with psychotic disorders and identify the factors associated with employment.Patients and methods: The study population comprised 406 patients with psychotic disorders who completed a forensic outpatient treatment order, were aged discharge from a forensic psychiatric ward and provided written informed consent. Psychotic disorders were defined as psychiatric disorders classified into F2 in the International Statistical Classification of Diseases and Related Health Problems, 10th edition. Demographic data were collected from the medical records of the inpatient treatment period. Prognostic data during the outpatient treatment order period was provided by the reintegration coordinators responsible for coordinating the patients’ social environment during this period. Exploratory univariate and multivariable logistic regression analyses identified the factors associated with employment. Results: The mean age at discharge was 44.4±10.8 years. The mean follow-up period was 2.69±1.01 years. There were 4.6 times more men (n=334) than women (n=72). During the outpatient treatment order period, 56 of 406 participants achieved employment (13.8%). Participants who committed serious crime, including homicide, arson, robbery, and sexual assault, had a lower employment rate compared to participants who committed bodily injury crimes (multivariable odds ratio, 0.421; 95% confidence interval, 0.220–0.807). History of substance use and living with family after discharge from a forensic psychiatric ward positively contributed to employment. Conclusion: The employment rate among forensic psychiatric outpatients with psychotic disorders was low and was similar to that reported in previous studies on general psychiatric patients with schizophrenia. Furthermore, serious criminal behavior negatively impacted employment.Keywords: criminal behavior, schizophrenia, work, job, mentally disordered offenders